Périphéricité et ultrapériphéricité insulaires dans l’Union européenne - André-Louis Sanguin (L'Espace Politique)
The EU’s peripheral and ultraperipheral islands issue appeared with the successive membership of maritime states and with the official EEZ implementation in 1994. From now on, EU has a territorial projection which is located beyond the continental Europe boundaries. This paper follows the official islands classification established by the European Commission. The question is whether the islands are fitting into the center-periphery relation. The situation of island peripheries and ultraperipheries improved but some recurrent problems are remaining. Islands are the matter of a twin link with their belonging state and with EU. Nowadays, they are acting as a new EU border which is different from classical borders of the old continent.